A theoretical forgetfulness: about some possible joints between video game studies and iconology - Maté, Diego (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The Game Studies field, dedicated to recreational phenomena, emerged at the beginning of the new millennium and, in just two decades of existence, regularized a large number of lines of research, approaches and methodologies, often in dialogue with psychoanalysis, the Sociology, cultural studies or aesthetics, among others. However, the Game Studies did not pay almost attention to iconology, a perspective they have in Aby Warburg's work a starting point and that would be continued, in turn, by authors such as Panofsky or Gombrich first, and later recovered by others by others such as Didi-Huberman, Agamben or Burucúa.The problematization of the ways in which the video game takes up issues as previously encoded by culture involves the phase of Warburguian concepts, such as that of Pathosformel, with specific dimensions of the video language, as the deployment of objectives whose overcoming organizes the interaction, thus building an enunciatory invested with skills that must be vehiculous to meet the goals presented.This articulation opens a series of issues: how does the constant update of the issues and the "pathos formulas" affect the playful interactivity? What insistence and reconfigurations can occur when historical projection reasons are invoked by a video game? These questions, involve methodological or conceptual adjustments regarding traditional definitions of topic and motive, or redefinitions of ludological notions?This work proposes an attempt exploration of these questions through some deployments in the video game of the researcher's figure, which includes that of the detective, set in the literature of the nineteenth century, but that overflows it, both forward (in ways and the of the journalist, the doctor or the superhero) as towards the past, and which had many appearances and reinventions in the video production.